Long-term safety and effectiveness of linagliptin as add-on therapy in Japanese patients with type 2 diabetes: final results of a 3-year post-marketing surveillance. Issue 3 (4th March 2021) - Ito, Tomohiro; Naito, Yusuke; Shimmoto, Naoki; Ochiai, Kaori; Hayashi, Naoyuki; Okamura, Tomoo
ABSTRACT: Background: We investigated the long-term safety and effectiveness of linagliptin in Japanese type 2 diabetes (T2D) patients starting linagliptin add-on therapy in routine clinical practice. Research design and methods: This 3-year prospective, observational, post-marketing surveillance (PMS) was conducted in Japanese patients starting linagliptin add-on therapy. The primary outcome was the incidence of adverse drug reactions (ADRs). The secondary outcome was the change from baseline in HbA1c. Results: The safety analysis set comprised of 3, 372 patients. Mean ± standard deviation (SD) age was 66.5 ± 12.4 years. Most patients (63.2%) received linagliptin in combination with another antidiabetic drug, most commonly a sulfonylurea (38.6%). The incidence of ADRs was 11.39%; the most common ADRs according to MedDRA preferred terms were diabetes mellitus (1.25%), hypertension (0.83%), and hypoglycemia (0.80%). In the effectiveness analysis set (n = 3, 029), mean ± SD HbA1c was 7.76 ± 1.37% at baseline and 7.26 ± 1.19% at last observation; mean change from baseline to last observation was – 0.49 ± 1.33%; sustained reductions in HbA1c were observed. These results were consistent across patient subgroups. Conclusions: In this PMS, linagliptin add-on therapy for Japanese T2D patients had a safety profile consistent with its known profile and HbA1c reductions over 3 years were observed. ClinicalTrials.gov: NCT01904383